PENGARUH METODE TAKRIR TERHADAP KEMAMPUAN SISWA DALAM MENGHAFAL AL-QUR'AN - Br. Sinaga, Denna Syahira; Lubis, Rahmat Rifai (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the effect of the takrir method on the ability of eighth-grade students at MTs Muallimin Univa Medan to memorise the Qur'an in the 2024/2025 academic year. The takrir method is a method that emphasises continuous repetition of the material being studied and is one of the methods that efficiently used in memorising the Qur'an. This study employs a quantitative approach using a quasi-experimental method and a one-group pre-test–post-test design. The sample consisted of 30 eighth-grade students divided into an experimental group and a control group. Data collection instruments included a multiple-choice test on Surah An-Naba’ verses 1-20 (20 questions), observation, and documentation. The research results showed that: the pretest and posttest scores in the experimental group improved after applying the takrir method. The average post-test score reached 86.6 and the pre-test score was 70.0. The hypothesis testing used a t-test with a significance level of 0.05. There was a significant improvement in the ability to memorise the Qur'an in the experimental class after applying the takrir method, with a significance of 0.036 < 0.05 and tcount 2.198 > ttable 2.048. Therefore, Ha is accepted and Ho is rejected. This study shows that the takrir method, structurally integrated into the tahfizh learning process, can serve as a practical and effective solution to enhance students' memorisation abilities.